Using TGT Technique to Improve the Seventh Graders' English Vocabulary at SMP 1 PSKD Jakarta - Marbun, Saputra Marisi Holong (JET (Journal of English Teaching), 2017)
AbstractThe method used in this research was action research applied in two cycles. This research was conducted to improve the Seventh Graders’ English vocabulary in SMP 1 PSKD, Jakarta. The 24 students of the seventh grade who participated in this study were taught vocabularies by using the TGT technique. The quantitative data, collected using tests, were analyzed by using the independent and paired sample t-test on SPSS version 22 program. The qualitative data, collected using the researchers’ diary notes, questionaire, open ended question sheets, and observation sheets, were analyzed descriptively. The results indicated that the TGT technique improved the participants’ English vocabulary, as shown by the increase of the mean scores of the tests conducted, i.e. the pre-test 55,94 (12,5%) increased to 66,81 (50%) of post-test of cycle I and to 83,23 (87,5%) of the post-test of cycle II. The statistical test also indicated that the use of TGT significantly increased the students’ English vocabulary. Based on the findings, it could be concluded that the use of TGT technique was effective to improve the seventh grade students’ English vocabulary. Keywords: action research, vocabulary, teams games tournament